Analysis of the relationship between the use of working capital and financial performance - Elkana Butar-Butar (Journal on Economics, Management and Business Technology, 2023)
This study aims to see the close relationship between the use of working capital and financial performance in food and beverage companies from 2002 to 2006. The type of research used is an empirical study. Data collection techniques using the documentation method. In this analysis, the steps used are: (1) calculating the level of working capital turnover, (2) calculating company profitability, (3) looking for the relationship between working capital turnover and financial performance. To find out the relationship between working capital turnoveThis study aims to see the close relationship between the use of working capital and financial performance in food and beverage companies from 2002 to 2006. The type of research used is an empirical study. Data collection techniques using the documentation method. In this analysis, the steps used are: (1) calculating the level of working capital turnover, (2) calculating company profitability, (3) looking for the relationship between working capital turnover and financial performance. To find out the relationship between working capital turnover and financial performance, correlation analysis techniques are used. The results of the study show that the efficiency of working capital as seen from working capital turnover is related to financial performance as seen from ROI. This can be seen from the significance level between working capital turnover and ROI which is 0.001. ROI has a relationship with the level of working capital turnover because the significance level is less than 0.01.r and financial performance, correlation analysis techniques are used. The results of the study show that the efficiency of working capital as seen from working capital turnover is related to financial performance as seen from ROI. This can be seen from the significance level between working capital turnover and ROI which is 0.001. ROI has a relationship with the level of working capital turnover because the significance level is less than 0.01.